2018
DOI: 10.1186/s12284-018-0250-1
|View full text |Cite
|
Sign up to set email alerts
|

A semi-dominant mutation in a CC-NB-LRR-type protein leads to a short-root phenotype in rice

Abstract: The mechanisms of plant defense against pathogen attack in plant leaves have been extensively studied. However, our understanding of plant defense mechanisms in plant roots is still limited. In this study, a semi-dominant mutant nrtp1-D (necrotic root tip 1), with a short-root phenotype, was characterized in rice. Map-based cloning revealed that NRTP1 encoded a typical coiled-coil nucleotide binding leucine rich repeat (CC-NB-LRR) type protein and the mutation caused an amino acid substitution in the Nucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In the long-term evolutionary process, plants have established complex and diverse resistance response systems to resist the invasion of pathogens and insects. However, the abnormality of plant defense response disturbs the balance between plant growth and resistance response, resulting in a variety of abnormal phenotypes, such as lesion mimic leaf, spotted leaf, shorter root, hybrid weakness, and so on [ 15 , 38 , 39 , 40 , 41 , 42 , 43 ]. Therefore, plants must coordinate the balance between immune response and growth in a constantly changing environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the long-term evolutionary process, plants have established complex and diverse resistance response systems to resist the invasion of pathogens and insects. However, the abnormality of plant defense response disturbs the balance between plant growth and resistance response, resulting in a variety of abnormal phenotypes, such as lesion mimic leaf, spotted leaf, shorter root, hybrid weakness, and so on [ 15 , 38 , 39 , 40 , 41 , 42 , 43 ]. Therefore, plants must coordinate the balance between immune response and growth in a constantly changing environment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, plants must coordinate the balance between immune response and growth in a constantly changing environment. The previous studies have shown that the proteins containing NB-ARC and LRR domains play key roles in the maintenance of the autoinhibited state, and the mutations of these domains activates plant defense responses [ 38 , 39 , 40 , 41 ]. NRTP1 encodes a typical coiled-coil nucleotide-binding leucine-rich repeat (CC-NB-LRR)-type protein, and its semi-dominant mutant showed defense response characteristics and exhibited shorter roots [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NB-ARC domain acts as a nucleotide-binding pocket and hydrolyzes adenosine triphosphate (ATP) to induce conformational changes in NB-LRR proteins and plays an important role in controlling protein activity. It has been reported that it controls several brown planthopper (BPH) resistance genes that are also defense-related phenotypes [51,52]. According to the known function of Os01g0269800 in plant defense mechanisms, it is not clearly understood that the association of Os01g0269800 is involved in mesocotyl elongation.…”
Section: Discussionmentioning
confidence: 99%
“…Agroinfiltration assay was performed in young leaves of N. benthamiana as previously described (Bruce et al, 2011;Yu et al, 2018). Briefly, 10 ml of A. tumefaciens GV3101 carrying pCVA/KK, pCVA/KSK or pCVB, a Cabbage leaf-curl geminivirus (CLCV)-based vector (Tang et al, 2010; were cultured to 0.6-0.8 OD600.…”
Section: Agroinfiltration Assaymentioning
confidence: 99%